2018
DOI: 10.1111/nph.15231
|View full text |Cite
|
Sign up to set email alerts
|

A noncoding RNA transcribed from the AGAMOUS (AG) second intron binds to CURLY LEAF and represses AG expression in leaves

Abstract: Dispersed H3K27 trimethylation (H3K27me3) of the AGAMOUS (AG) genomic locus is mediated by CURLY LEAF (CLF), a component of the Polycomb Repressive Complex (PRC) 2. Previous reports have shown that the AG second intron, which confers AG tissue-specific expression, harbors sequences targeted by several positive and negative regulators. Using RACE reverse transcription polymerase chain reaction, we found that the AG intron 2 encodes several noncoding RNAs. RNAi experiment showed that incRNA4 is needed for CLF re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 48 publications
0
55
1
Order By: Relevance
“…Knockdown of AG-lincRNA4 resulted in AG activation in leaves by lowering the H3K27me3 level at the AG locus. Consequently, the corresponding mutant showed phenotypes resembling those of ectopic AG expression (Wu et al 2018 ). LDMAR was identified in rice through map-based cloning and regulates photoperiod-sensitive male fertility via RdDM (Ding et al 2012a , b ; Zhou et al 2012 ).…”
Section: Functions and Molecular Mechanisms Of Lncrnas In Plantsmentioning
confidence: 99%
“…Knockdown of AG-lincRNA4 resulted in AG activation in leaves by lowering the H3K27me3 level at the AG locus. Consequently, the corresponding mutant showed phenotypes resembling those of ectopic AG expression (Wu et al 2018 ). LDMAR was identified in rice through map-based cloning and regulates photoperiod-sensitive male fertility via RdDM (Ding et al 2012a , b ; Zhou et al 2012 ).…”
Section: Functions and Molecular Mechanisms Of Lncrnas In Plantsmentioning
confidence: 99%
“…Based on ChIP, ChIP-qPCR, RIP, and other experiments, several lncRNAs mentioned above, including COOLAIR, COLDAIR, APOLO, ELENA, DRIR, SVALKA, ASCO-lncRNA, MAS and LDMAR, are all classically regulated through epigenetic regulation. Moreover, Wu et al [69] found that the methylation level of H3K27me3 in Arabidopsis AG-incRNA4 RNAi was significantly lower than that of the control by performing ChIP-seq. The RNA-pulldown and RIP techniques were used to further reveal that the sense strand of AG-incRNA4 can directly bind to the CURLY LEAF (CLF) protein.…”
Section: Epigenetic Regulation Of Lncrnamentioning
confidence: 99%
“…Adding 35S enhancer can extend the tissue specificity of NtAGIP1 from inner whorls of flower (stamens and carpels) to the outer whorls (sepals and petals), but the activity of 35SNtA-GIP1 does not cross the boundary of flower organs. An array of factors is responsible for the repression of AG [44,45]. For example, APETALA2 is involved in the repressing the expression of AG in the outer floral whorls through recruiting the histone deacetylase HDA19, thus…”
Section: Plos Onementioning
confidence: 99%
“…Importantly, GAGA factor binding motif has been found to be involved in the recruitment of PRC2 in both Arabidopsis and Drosophila. Recently, Wu and colleagues reported that a DNA region within Arabidopsis AG intron 2 (+2616 to +3348) is involved in the recruitment of PRC2 to represses AG expression in leaves via the transcribed noncoding RNA [45]. They pointed out that the identified DNA region also contains PREs which may recruit PRC2.…”
Section: Plos Onementioning
confidence: 99%